Expanding the phenotypic and genetic spectrum of Chinese patients with congenital absence of vas deferens bearing CFTR and ADGRG2 alleles. (27th February 2019) - Yuan, P.; Liang, Z. K.; Liang, H.; Zheng, L. Y.; Li, D.; Li, J.; Zhang, J.; Tian, J.; Lai, L. H.; Zhang, K.; He, Z. Y.; Zhang, Q. X.; et al.
Abstract: Background: Congenital absence of vas deferens (CAVD) is a major cause of obstructive azoospermia. Mutations in CFTR and ADGRG2 are responsible for this disease. However, until now the genetic spectrum of the CFTR and ADGRG2 genes in Chinese population and the reasons of the differences from Caucasian cohorts were not clear. Objectives: (i) To study the characteristic and functional consequences of CFTR and ADGRG2 mutations in Chinese CAVD patients. (ii) To describe the genetic spectrum of Chinese CAVD patients and explain the reasons of the differences from Caucasian cohorts and Chinese cystic fibrosis (CF) patients. Materials and Methods: Patients were screened for mutations in CFTR by Sanger sequencing. Patients with only one or no mutations were further investigated by multiplex ligation‐dependent probe amplification analysis and direct sequencing of ADGRG2 gene. Bioinformatic analysis and structural modeling of proteins were performed. Results: A total of 28 mutations in CFTR were identified in 72 patients, of which five mutations were novel. Fifty‐five patients (76.39%) had CFTR mutations but no indels, among which 80.00% CBAVD patients have at least one CFTR mutation and 66.67% CUAVD have at least one CFTR mutation. Two novel mutations (p.Lys818* and p.Arg1008Gln) in ADGRG2 were detected. These novel mutations were predicted to be damaging by bioinformatics and were absent or extremely low frequency among our controls and databases. The genetic spectrum of Chinese CAVD patients revealed that the most common mutations were c.1210‐12T[5], p.Ile556Val and p.Gln1352His, the last two of which were predicted to reduce the domains' contacts and weaken adenosine triphosphate binding. Discussion and Conclusion: This study illustrates the significance of all exon sequencing in CFTR and ADGRG2 . A picture of the genetic spectrum of Chinese CAVD patients and the most common mutations can be described, which are different from Caucasian cohorts and Chinese CF patients.